Al-Mathla’ Al-Sa’id Fii Hisabat Al-Kawakib ‘Ala Rashd Al-Jadid: melacak algoritma hisab awal bulan hijriyah - Taufik, Muhammad Faqih; Alwi, Ahmad Ihsan (UIN ALAUDDIN MAKASSAR, 2024)
The book Al-Mathla' Al-Said is one of the sources of the archipelago astronomical book. An interesting book to study. The reckoning used in the book is included in the category of true bi at-tahkik reckoning which uses the science of measuring spherical triangles in calculating data from the beginning of the month. The aim of this research is to trace the reckoning algorithm for the beginning of the Hijriyah month in the book Al-Mathla' Al-Said. The study in this research uses the library research method with descriptive analysis. The calculation results of the Al-Mathla' Al-Said book method are not much different from the results using contemporary reckoning. Apart from that, there is something unique about the book, namely the use of jumaliyah numbers in its astronomical tables.